Smoking behavior and its determinants among primary healthcare workers: A systematic review - Doni Juliana; Elviera Gamelia; Eri Wahyuningsih (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Smoking among primary healthcare workers remains an important public health concern because healthcare workers are expected to serve as role models and play a central role in tobacco prevention and smoking-cessation interventions. However, tobacco use persists among healthcare workers and may affect their credibility and engagement in providing smoking-cessation support to patients. Purpose: To identify the prevalence and determinants of smoking behavior among primary healthcare workers. Method: A systematic review of studies published between 2010 and 2026 was conducted using PubMed, Scopus, and ScienceDirect, following the PRISMA 2020 guidelines. A total of 193 articles were identified, of which nine cross-sectional studies involving primary healthcare workers met the inclusion criteria and were included in the review. Results: The included studies were conducted in Syria, Saudi Arabia, India, Jordan, Qatar, Italy, South Africa, and two regions of Iraq. The prevalence of smoking and tobacco use varied considerably across countries, professional groups, sex distributions, and operational definitions of tobacco use. Smoking prevalence was consistently higher among male than female healthcare workers. Smoking behavior was associated with multiple interconnected factors, including gender, professional and occupational characteristics, knowledge and attitudes, occupational stress, family and peer influences, social and workplace norms, enforcement of smoke-free policies, and the availability of smoking-cessation services. Although healthcare workers generally showed awareness of the harmful effects of tobacco and favorable attitudes toward tobacco control, a persistent knowledge, attitude, and practice gap was identified. Healthcare workers who smoked were also less likely to provide cessation counseling or support tobacco-control policies. High interest in quitting was reported among current tobacco users; however, limited cessation support, nicotine dependence, occupational stress, and environmental influences remained important barriers. Conclusion: Smoking among primary healthcare workers is influenced by individual, occupational, social, and organizational factors. Comprehensive interventions involving cessation support, stress management, professional training, and consistent smoke-free policies are needed.